A novel rescue therapy for cerebral vasospasm: Cisternal Nimodipine application via stereotactic catheter ventriculocisternostomy. (May 2019) - Roelz, Roland; Scheiwe, Christian; Coenen, Volker A.; Reinacher, Peter C.
Highlights: Stereotactic Catheter Ventriculocisternostomy (STX-VCS) creates a direct cisternal treatment access. Cisternal application of Nimodipine reverses cerebral vasospasm. DCI may be prevented by stereotactic catheter ventriculocisternostomy and cisternal spasmolysis. Abstract: Delayed Cerebral Infarction (DCI) due to Cerebral Vasospasm (CVS) is an important contributor to poor outcome after aneurysmal subarachnoid haemorrhage (aSAH). Despite established risk factors CVS and DCI are unpredictable at the individual patient level. Efficient treatments are lacking. We report a novel rescue therapy for DCI: Access to the basal cisterns by stereotactic catheter ventriculocisternostomy (STX-VCS) and direct cisternal application of the spasmolytic agent Nimodipine. On the basis of individual treatment decisions three aSAH patients who developed CVS underwent STX-VCS. Continuous lavage with Nimodipine was performed. CVS was assessed by daily transcranial doppler ultrasonography. Neurological outcome at 3 months was assessed by modified Rankin scale. STX-VCS was performed without complications in all patients. CVS rapidly resolved upon cisternal application of Nimodipine. CVS recurred in two patients upon interruption of Nimodpine application and resolved upon restart of Nimodipine. DCI did not occur in all three cases. STX-VCS and cisternal Nimodipine application is a novel rescue therapy for CVS treatment and DCI-prevention in patients with aSAH.